Reading the World through the Skin and Ears: A New Perspective on Sensory Substitution - DEROY, Ophelia; AUVRAY, Malika (Frontiers in Psychology, 2012)
Sensory substitution devices aim at replacing or assisting one or several functions of a deficient sensory modality by means of another sensory modality. Despite the numerous studies and research programs devoted to their development and integration, sensory substitution devices have failed to live up to their goal of allowing one to ‘see with the skin’ (White et al., 1970) or to “see with the brain” (Bach-y-Rita et al., 2003). These somewhat peremptory claims, as well as the research conducted so far, are based on an implicit perceptual paradigm. Such perceptual assumption accepts the equivalence between using a sensory substitution device and perceiving through a particular sensory modality.  Our aim is to provide an alternative model, which defines the sensory substitution as being closer to culturally-implemented cognitive extensions of existing perceptual skills such as reading. In this talk, we will show why the analogy with reading provides a better explanation of the actual findings, that is, both of the positive results achieved and of the limitations noticed across the field of research on sensory substitution. The parallel with the most recent two-route and interactive models of reading (e.g., Dehaene et al., 2005) generates a radically new way of approaching these results, by stressing the dependence of integration on the existing perceptual-semantic route. In conclusion, the present perspective questions the relevance of the term ‘sensory substitution‘ and enables us to generate innovative research questions and specific predictions which set the stage for future work.